Proposições metodológicas para desenvolvimento de vocabulário musical para improvisação em música popular instrumental brasileira com foco no trompete : Methodological propositions for the development of musical vocabulary for improvisation in Brazilian instrumental popular music with the focus on the trumpet - Brandão, Klesley Bueno, 1985- (2019)
Orientadores: Paulo Adriano Ronqui, Jorge Luiz Schroeder